Construction project management : a practical guide to field construction management. - Sears, S. Keoki (Wiley, 2015)
"A thoroughly updated edition of the classic guide to project management of construction projectsFor more than thirty years, Construction Project Management has been considered the preeminent guide to all aspects of the construction project management process, including the Critical Path Method (CPM) of project scheduling, and much more. Now in its Sixth Edition, it continues to provide a solid foundation of the principles and fundamentals of project management, with a particular emphasis on project planning, demonstrated through an example project, along with new pedagogical elements such as end-of-chapter problems and questions and a full suite of instructor's resources. Also new to this edition is information on the Earned Value Analysis (EVA) system and introductory coverage of Building Information Modeling (BIM) and Lean Construction in the context of project scheduling. Readers will also benefit from building construction examples, which illustrate each of the principles of project management. This information, combined with the case studies provided in the appendix, gives readers access to hands-on project management experience in the context of real-world project management problems. Features two integrated example projects--one civil and one commercial--fully developed through the text Includes end-of-chapter questions and problems Details BIM in scheduling procedures, Lean Construction, and Earned Value Analysis, EVA Provides teaching resources, including PowerPoint slides, interactive diagrams, and an Instructor's Manual with solutions for the end-of-chapter questions Construction Management and Civil Engineering students and professionals alike will find everything they need, to understand and to master construction project management in this classic guide"--